Faktor Determinan Sosial Mempengaruhi Manajemen Laktasi pada Ibu Hamil Diwilayah Kerja Puskesmas Kalumata Kecamatan Ternate Selatan Kota Ternate Tahun 2013 - Sulima Hamadun Gay (Jurnal Kesehatan, 2014)
Sulima Hamadun Gay*) Abstract : Lactation management for pregnant women is based on the consequences of the process of growth and development of the baby in the womb until the time of birth and during early life gold. This study aims to determine the relationship determinant with maternal lactation management working area Kalumata District Health Center South Ternate Ternate in North Maluku. In 2013.This type of research is a quantitative study with a cross-sectional study design. Large sample of 180 pregnant women first and second trimester. Data analysis was done by Chi Scuare test and correction by using logistic regression. The results showed that there is a relationship between knowledge (p = 0.000), compliance (p = 0.000), husband's support (p = 0.000), health care (p = 0.000), the ability of officers (p = 0.001), and the local culture p = 0.002) while there was no association of economic status (p = 0148) on the implementation of management of lactation in pregnant women. From this study it can be concluded that the bulk of the determinant factors related to the implementation of the management of lactation in pregnant women, therefore, required the participation or cooperation of all parties in order to increase coverage breastfeeding infants.